Penerapan Konsep Teori Model Sister Callista Roy pada Asuhan Keperawatan dengan Penyakit Sindrom Nefrotik - Farhan, Andi (AACENDIKIA: Journal of Nursing, 2024)
Nephrotic syndrome is a clinical and laboratory condition without indicating an underlying disease, which indicates glomerular inflammatory disorders. Functionally, nephrotic syndrome is caused by abnormalities in the filtration process in the glomerulus which usually causes various problems that require appropriate, fast and accurate treatment. The general aim of this case study is to implement the application of the concept of the Sister Callista Roy model theory to nursing care for Nephrotic Syndrome. The research method in this case study involves the application of a nursing process approach method based on the selected nursing theory. Data collection techniques were carried out through interviews, observation, physical examination, and implementation of nursing care. The data sources used involve primary data obtained directly from patients, and secondary data originating from families, health workers, as well as documentation of other examination results to carry out nursing care. The results of nursing care by applying the Sister Callista Roy model theory to nursing care for nephrotic syndrome is that skin integrity is maintained and healing of wounds in the scrotum occurs, there are no signs and symptoms of infection, clients are able to demonstrate effective coping with pain by using distraction and relaxation techniques. guided or independent, body fluids are in a balanced condition as indicated by the absence of edema and the absence of albumin in the urine, the client is able to demonstrate effective coping with feelings of anxiety or fear, and carry out activities independently according to his tolerance.